Metabolism, Energetics, and Lipid Biology in the Podocyte – Cellular Cholesterol-Mediated Glomerular Injury - Merscher, Sandra; Pedigo, Christopher E.; Mendez, Armando J. (Frontiers in Endocrinology, 2014)
Chronic kidney disease (CKD) is associated with a high risk of death. Dyslipidemia is commonly observed in patients with CKD and is accompanied by a decrease in plasma high-density lipoprotein (HDL), and an increase in plasma triglyceride-rich lipoproteins and oxidized lipids. The observation that statins may decrease albuminuria but do not stop the progression of CKD indicates that pathways other than the cholesterol synthesis contribute to cholesterol accumulation in the kidneys of patients with CKD. Recently, it has become clear that increased lipid influx and impaired reverse cholesterol transport can promote glomerulosclerosis, and tubulointerstitial damage. Lipid-rafts are cholesterol-rich membrane domains with important functions in regulating membrane fluidity, membrane protein trafficking, and in the assembly of signaling molecules. In podocytes, which are specialized cells of the glomerulus, they contribute to the spatial organization of the slit diaphragm under physiological and pathological conditions. The discovery that podocyte-specific proteins such as podocin can bind and recruit cholesterol contributing to the formation of the slit diaphragm underlines the importance of cholesterol homeostasis in podocytes and suggests cholesterol as an important regulator in the development of proteinuric kidney disease. Cellular cholesterol accumulation due to increased synthesis, influx or decreased efflux is an emerging concept in podocyte biology. This review will focus on the role of cellular cholesterol accumulation in the pathogenesis of kidney diseases with a focus on glomerular diseases.